Characterization of Empty Fruit Bunch of Palm Oil as Co-firing Biomass Feedstock - Rusdianasari Rusdianasari; Iwan Arissetyadhi; Leila Kalsum; Yohandri Bow; Aida Syarif; Fatahul Arifin (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Empty fruit bunches of Palm Oil (EFB) are a potential source of biomass energy because they contain lignocellulose (cellulose, hemicellulose and lignin) so that they can be converted into biopellets for co-firing. The purpose of this research is to determine the raw material properties of EFB in the form of proximate, ultimate, lignin, and biopellets. Using a pelletizer, biopellets are created by adding starch as an adhesive. The raw material characteristics of EFB from proximate analysis revealed moisture content of 11.98%, ash content of 6.53%, volatile matter content of 65.15%, and fixed carbon content of 16.44%. According to the final study results, the biopellets from empty fruit bunches included 48.53% C, 6.05% H, 0.32% N, 36.8% O, and 0.08% Sulphure. The atomic ratio obtained from the final analysis results could be used to determine the calorific value that can be used for fuel; the biopellet calorific value of EFB is 4,583 kcal/kg, with Hardgrove Grindability Index (HGI) values of 78.6 and Ash Fusion Temperature (AFT) 1100oC. The lower the value of the atomic ratio contained, the higher the calorific value contained in a specific fuel.